Contact of Wheel and Rail in Computer Simulation of Vehicle Dynamics and Axle Drive Dynamics - Oldrich Polach (Communications - Scientific letters of the University of Zilina, 2001)
In computer simulations different methods are used to calculate tangential wheel-rail forces in vehicle dynamics and in the analysis of traction systems. For the simulation of vehicle dynamics and drive dynamics interaction, the varying methods have to be combined into one method. Using the friction coefficient decreasing with increasing slip velocity between wheel and rail, decreasing part of creep-force function behind the adhesion limit as well as various adhesion conditions can be taken into account in the vehicle dynamics simulations.The proposed method of wheel-rail forces calculation was tested using an ADAMS/Rail model of a four axle locomotive. The curving simulations with a varying tractive force show the influence on the wheel-rail forces distribution. A simulation of the adhesion test demonstrates the applicability of the proposed method for investigations of drive dynamics and vehicle behaviour interaction.